Decoding Myosin-3 mutational hotspots: Linking deleterious variants to Duchenne muscular dystrophy severity and psychiatric comorbidities - Mohammed Ageeli Hakami; Ahad Amer Alsaiari; Taj Mohammad; Anas Shamsi (PLoS ONE, 2025)
Duchenne muscular dystrophy (DMD) is a severe neuromuscular disorder primarily caused by mutations in the dystrophin gene, leading to progressive muscle degeneration. While the loss of dystrophin is central to DMD pathogenesis, impaired muscle regeneration further exacerbates disease severity. As MYH3-encoding Myosin-3 is involved in muscle development and regeneration, we examined how it could be added to the list of possible contributors to DMD pathology. This study employed various computational tools such as PolyPhen-2, SIFT, and I-Mutant to analyze 486 MYH3 missense mutations and predict the structural and functional implications. We discovered 89 deleterious substitutions, of which 80 were pathogenic. Of these, 45 mutations were identified as likely to pathogenically alter Myosin-3 solubility, and 5 (G182A, R244C, R244H, H285Y, N483S) fell within evolutionarily conserved regions. The mutant G182A is of particular interest as it lies within the ATP-binding site, which may lead to an impairment of energy-dependent myosin activity. These mutations likely impair muscle regeneration, potentially intensifying the severity of dystrophy. Furthermore, we hypothesize that these functional deficiencies may not be limited to muscle pathogenesis and could be related to the development of neuropsychiatric comorbidities observed in DMD, although this remains to be experimentally confirmed. Our results emphasize the relevance of Myosin-3 in the pathogenesis of DMD and the importance of combined research on neuromuscular and psychiatric aspects to improve therapeutic approaches.